Dynasty Control of the Process of Forming Coalition of Political Parties in the 2020 Cilegon Local Leaders Election - Riyansyah, Abdul; Ferliana, Ferliana; Mayrudin, Yeby Ma'asan; Godjali, Moh. Rizky (HK-Publishing, 2021)
Abstract This paper discusses the power of political dynasties in Cilegon in the process of forming a coalition of political parties in the 2020 Pilkada. The embodiment of political dynasties continues to be accommodated to perpetuate power by putting aside the track record of organizing experience both in parties and in state institutions. The theory used in this study is the theory of political dynasties and party coalitions. The research method uses a qualitative study with an explanatory case study approach. The focus of this study is to explain how coalition maps are formed and how the influence of dynasties on political parties. The results of this study indicate that the strong influence of political dynasties in Cilegon arises because of the power that has been held since Cilegon City was founded after Banten officially became a province. At that time the elected mayor was Tubagus Aat Syafaat and continued with his sons Tubagus Iman Ariyadi and Ratu Ati Marliati until the 2020 Local Leader Election. The family mainly used the Golkar Party and lower-middle parties to perpetuate their power to form the Minimum Winning Coalition model so that passed the nomination process. Keywords: political dynasty; party coalition; pilkada; cilegon cityAbstrak Tulisan ini membahas kekuatan dinasti politik yang ada di Kota Cilegon dalam proses pembentukan koalisi partai politik di Pilkada tahun 2020. Pengejawantahan dinasti politik terus diakomodasi untuk melanggengkan kekuasaan dengan menyampingkan rekam jejak pengalaman pengorganisasian baik di partai maupun di kelembagaan negara. Teori yang digunakan dalam penelitian ini adalah teori dinasti politik dan koalisi partai. Adapun metode penelitian menggunakan kualitatif dengan pendekatan studi kasus eksplanatoris. Fokus kajian ini yaitu mengupas tentang bagaimana peta koalisi terbentuk dan bagaimana pengaruh dinasti terhadap partai-partai politik. Adapun hasil penelitian ini menunjukkan bahwa pengaruh kuat dari dinasti politik di Cilegon muncul akibat dari kekuasaan yang dimiliki sejak Kota Cilegon berdiri setelah Banten resmi menjadi Provinsi. Saat itu yang terpilih sebagai Walikota yaitu Tubagus Aat Syafaat dan dilanjut dengan anaknya Tubagus Iman Ariyadi dan Ratu Ati Marliati sampai pada saat Pilkada 2020. Keluarga tersebut memanfaatkan utamanya Partai Golkar dan partai-partai menengah-bawah untuk melanggengkan kekuasaannya untuk membentuk model Minnimal Winning Coalition agar lolos proses pencalonannya. Kata Kunci: dinasti politik; koalisi partai; pilkada; kota cilegon